Pelatihan Penerapan Strategi Pembelajaran Inklusif Bagi Guru Sekolah Dasar dalam Upaya Identifikasi Siswa Berkebutuhan Khusus - Alfian, Alfian; Santosa, Imam; Surya Saputra, Deny (PELITA NUSA TENGGARA, 2025)
This study aims to describe the effectiveness of training on the application of inclusive learning strategies for elementary school teachers in identifying students with special needs. The background of the study is based on the necessity to enhance teachers’ competencies in creating inclusive learning environments and the importance of early identification of students with special educational needs to ensure appropriate support and services. This research employs a descriptive qualitative approach through training activities attended by elementary school teachers. Data were collected through observation, interviews, and document analysis. The findings indicate that the training significantly improved teachers’ knowledge and skills in recognizing the characteristics of students with special needs and in designing adaptive and responsive learning strategies. These results suggest that training in inclusive learning strategies is a strategic step in supporting the successful implementation of inclusive education at the elementary level.